Investigation of tool life and surface integrity when drilling Ti-6A1-4V and Ti-5A1-4V-Mo/Fe. - Abd. Rahim, Erween; Sharif, Safian (The Japan Society of Mechanical Engineers, 2006)
Machinability study on the drilling of two alpha beta titanium alloy series, Ti-6Al-4V and Ti-SAl-4V-0.6Mo-0.4Fe were conducted using an uncoated carbide drill. The effect of cutting speed on tool life, tool failure mode, cutting force and surface integrity of the drilled surface were discussed. Results showed that Ti-6Al-4V exhibited a more superior machinability property when compared to the Ti-5Al-4V Mo/Fe alloy system. The tool wear progression when drilling Ti-6Al-4V was lower than that of Ti-5Al-4V Mo/Fe. The tool experienced similar failure mechanisms which were non uniform wear and chipping when drilling both alloys. At high cutting speed and after prolonged machining, excessive plastic deformation was observed on the subsurface layer of the drilled surface which resulted in increase in the hardness value.